Anthropometric Indicators Of Teenagers Of Military Conscription Age In Different Regions Of Karakalpakstan - Rzaev Raxat Muratbaevich; Khalmuratova Jumagul Mafurovna (Zien Journals, 2023)
In the region of Karakalpakstan, great attention is paid to the development of measures to improve physical development indicators and to adapt the body of teenagers of military draft age to the adverse environmental factors of the external environment. In this regard, the purpose of our article entitled "Anthropometric parameters of youths of military draft age in different regions of Karakalpakstan" is to determine the dynamics of anthropometric and morphofunctional parameters in youths of military draft age depending on the somatic type. Adolescents of military conscription age based on goals and duties
Keywords: anthropometric indicators; dynamics; physical development